Sperm Competition in Fish - Fitzpatrick, John L. (My University, 2008)
Sperm competition, the contest between sperm from rival males for fertilizations, is an important evolutionary force shaping sperm characteristics. Theory predicts that males experiencing elevated levels of sperm competition will invest more in sperm number, size and speed. While broad support exists for the idea that elevations in sperm competition lead to increased investment in sperm production, there is mixed support for the role of sperm competition in shaping sperm size and swimming speed. In this thesis, using a combination of within-species and comparative studies, I describe how sperm competition has influenced sperm traits in fishes and critically test a number of predictions from sperm competition theory. In the marine plainfin midshipman fish (Porichthys notatus) and the fresh-water shell brooding cichlid Telmatochromis vittatus, I show that the males who experience the highest level of sperm competition had faster but not longer sperm. Instead, selection appears to have acted on sperm energetics, increasing energy production to drive sperm movement in males who experience more intense levels of sperm competition. In a comparative study using Tanganyikan cichlids, I show that males in species experiencing high levels of sperm competition (i.e. promiscuous species) had both longer and faster sperm than males of closely related species unlikely to experience sperm competition (i.e. monogamous species). I also uncovered a predicted but previously inadequately tested relationship between sperm size and speed. This relationship holds across, but not within, species and I discuss possible explanations for differences between and within species. Finally, I used directional tests of trait evolution to assess how selection acts to increase sperm swimming speed and provide evidence that the evolution of fast swimming sperm preceded the evolution of long sperm across cichlid fishes. Together, the results of this thesis show that spenn competition promotes the evolution of faster swimming spenn in fishes and highlights the importance of sperm energetics in detennining the competitive success of ejaculates.
Keywords: sperm competition; males; fertilization; sperm traits